Priprava feroelektričnih tankih plasti iz raztopin - Malič, Barbara (Vakuumist, 1997)
Research of ferroelectric thin films has noted a marked increase due to a possibility of various microelectronic, optoelectronic and micromechanic applications. The materials, processing and possible applications of ferroelectric thin films are presented. Sol-gel processing of ferroelectric thin films is disucussed in more detail.
Keywords: tanke plasti; feroelektriki; uporaba